The Remote Professor: Making Academia Work for Working Mothers - Weaver, Jennifer M. (Journal of the Motherhood Initiative for Research and Community Involvement, 2025)
This article explores the intersection of motherhood and academia, highlighting the struggles of working mothers in higher education and offering a model for incorporating remote work into academia. Drawing upon the literature on both academic motherhood and remote work, the author integrates the literature to argue that remote work can offer an innovative path for academic mothers seeking to manage all facets of their responsibilities. Commenting on the greedy institutions of both motherhood and academia, which demand total commitment, the author argues that academia, historically structured to favour men, must evolve to accommodate the realities of modern caregiving, particularly for women. Remote work can provide flexibility, autonomy, and geographic mobility for mothers as they manage the demands of caregiving while meeting the responsibilities of teaching, research, and service inherent to the faculty role. However, creating effective remote positions must be done with care, as it is incumbent upon university chairs and administrators to address biases in determining who is offered remote roles. They must also work to mitigate challenges with remote work, such as feelings of isolation, lack of connection, and under-appreciation. To counteract these issues, academic chairs can support remote employees by maintaining regular communication, making them feel valued, and fostering a departmental culture that supports in-person and remote members equally. Rethinking work structures in academia through remote faculty positions presents an innovative way to ensure all faculty members, not just some, can thrive.